2021
DOI: 10.3389/fphar.2021.764297
|View full text |Cite
|
Sign up to set email alerts
|

A Herbal Mixture Formula of OCD20015-V009 Prophylactic Administration to Enhance Interferon-Mediated Antiviral Activity Against Influenza A Virus

Abstract: OCD20015-V009 is an herbal mix of water-extracted Ginseng Radix, Poria (Hoelen), Rehmanniae Radix, Adenophorae Radix, Platycodi Radix, Crataegii Fructus, and Astragali Radix. In this study, its in vitro and in vivo antiviral activity and mechanisms against the influenza A virus were evaluated using a GFP-tagged influenza A virus (A/PR/8/34-GFP) to infect murine macrophages. We found that OCD20015-V009 pre-treatment substantially reduced A/PR/8/34-GFP replication. Also, OCD20015-V009 pre-treatment increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The components that exert the antiviral effect of TCMs are mainly through single components and multiple components [22][23][24]. OCD20015-V009 is an herbal mix of water-extracted Ginseng Radix, Poria (Hoelen), Rehmanniae Radix, Adenophorae Radix, Platycodi Radix, Crataegii Fructus, and Astragali Radix [25], and chlorogenic acid and ginsenoside Rd are the dominant antiviral components that stimulate the antiviral response in murine macrophages and mice to viral infections. It was found that many TCM monomers or compound preparations exhibited multichannel antiviral effects in vitro, and the safe concentration was within the range of doses to achieve a better antiviral effect.…”
Section: Introductionmentioning
confidence: 99%
“…The components that exert the antiviral effect of TCMs are mainly through single components and multiple components [22][23][24]. OCD20015-V009 is an herbal mix of water-extracted Ginseng Radix, Poria (Hoelen), Rehmanniae Radix, Adenophorae Radix, Platycodi Radix, Crataegii Fructus, and Astragali Radix [25], and chlorogenic acid and ginsenoside Rd are the dominant antiviral components that stimulate the antiviral response in murine macrophages and mice to viral infections. It was found that many TCM monomers or compound preparations exhibited multichannel antiviral effects in vitro, and the safe concentration was within the range of doses to achieve a better antiviral effect.…”
Section: Introductionmentioning
confidence: 99%
“…Astragaloside IV (AsIV), an active ingredient derived from A. membranaceus, is known as a signature compound for its various excellent biological activities (Zhou et al 2012), including anti-in ammatory, antioxidant, neuroprotective and anti-cancer effects(Luo, Wu, and Li 2021; Shahrajabian, Sun, and Cheng 2019). Studies have shown that AsIV is not only an excellent immunomodulator but in some aspects even surpasses ginsenosides (Zheng et al 2020), and is of great value in the treatment of cardiovascular and cerebrovascular diseases, respiratory diseases, diabetes and related complications (Facioni et al 2018; Kwon et al 2021). AsIV, despite its natural origin and excellent effects, has poor solubility and stability, resulting in low value adding products and limiting its direct application in solid formulations.…”
Section: Introductionmentioning
confidence: 99%